Effective Inclusion Strategies for Professionals Working with Students with Disabilities - Hogan, Kathleen A.; Lohmann, Marla; Champion, Rose (Journal of the American Academy of Special Education Professionals, 2013)
Inclusive classrooms are now the norm in many K-12 public schools across the United States. General education teachers have a difficult job making sure all their students are meeting state standards. With the addition of special education students in the classroom, their job becomes even more difficult due to meeting the needs of the general education students, as well as meeting the academic and behavioral needs of special education students. A student’s general and special education teacher need to learn effective collaboration strategies with other educational professionals and parents. The purpose of the article is to provide collaboration strategies to help make the general education teachers’ job a little less difficult.